Pentingnya Menjaga Kelestarian Lingkungan Ditengah Maraknya Eksploitasi Sumber Daya Alam melalui Implementasi Green History Pembelajaran Sejarah - Nurdiantie, Annida Syahida (Lembaga Yasin AlSys, 2023)
In the midst of the high needs of humans who depend on nature, many problems occur in the human environment. The main problem of the environment is the result of the continuous exploitation of natural resources due to the insistence on human needs which can damage the earth and the low character of environmental concern owned. Using the literature review method, the author examines the sources that have been obtained and then the sources are collected, then reviewed one by one with other sources as additional reference material so that the information obtained is broader and maximized then criticizes and provides views related to the materials in accordance with the author's understanding. The importance of preserving the environment means having awareness, concern, or attitude to always heed something that happens around humans, namely in the environment where they live. One of the efforts that can be made to grow this awareness is through the learning process, especially history learning through the implementation of Green History which in education has a lot of space to shape the character of students. History learning that is integrated with the conditions of the current environmental picture can increase students' awareness and understanding of the importance of preserving the environment amid the rampant environmental damage that occurs.